Introduction to reference work: Vol II : Reference Services - William A. Katz (New York : McGraw-Hill Book Co, 1969)
"Basic Information Services, Volume I" of "Introduction to Reference Work", explains the basic reference processes and sources of information in today's libraries. It is a tool for understanding and mastering basic reference forms, no matter how they're packaged.
Index
aia 28/6/17
Loans
Keywords: Reference books--- Bibliography; Reference services(Libraries)